Applying multiple proteases to direct digestion of hundred‐scale cell samples for proteome analysis. (5th July 2015) - Chen, Qi; Yan, Guoquan; Zhang, Xiangmin
<x xml:space="preserve">Abstract</x> Rationale Analyzing the proteome on the scale of only several hundred cells with mass spectrometry has great significance for applications with limited sample amounts. We applied multiple proteases to the direct digestion of cells and compared the identified proteins both qualitatively and quantitatively. Methods Three hundred cells were directly digested by trypsin, chymotrypsin, or the combination of trypsin and chymotrypsin. The peptides were identified using a LTQ‐Orbitrap XL, and data were analyzed using MaxQuant software. Results Different proteases produced different identified protein numbers. Trypsin proved to be the best choice for generating the largest protein number, while other proteases complemented the identification results of trypsin by increasing protein sequence coverage. Concerning the quantitative perspective, using trypsin would produce the biggest number of proteins quantifiable by intensity‐based absolute quantification (iBAQ). Conclusions When hundred‐scale cell samples are analyzed, an optimum choice of proteases should be made to realize different analytical objectives. Copyright © 2015 John Wiley & Sons, Ltd.